Structural, mechanical and chemical evaluation of molar-incisor hypomineralization-affected enamel: A systematic review - Elhennawy, Karim; Manton, David John; Crombie, Felicity; Zaslansky, Paul; Radlanski, Ralf J.; Jost-Brinkmann, Paul-Georg; Schwendicke, Falk (Archives of oral biology, 2017)
•Structural, mechanical and chemical properties of MIH-enamel were assessed.•Mineral quantity, quality, hardness and elasticity were reported to be reduced.•The association between appearance and severity are not clear.•Heterogeneity in current research findings was found.•Standard protocols and outcome measures in future studies are needed. To systematically assess and contrast reported differences in microstructure, mineral density, mechanical and chemical properties between molar-incisor-hypomineralization-affected (MIH) enamel and unaffected enamel. Studies on extracted human teeth, clinically diagnosed with MIH, reporting on the microstructure, mechanical properties or the chemical composition and comparing them to unaffected enamel were reviewed. Electronic databases (PubMed, Embase and Google Scholar) were screened; hand searches and cross-referencing were also performed. Twenty-two studies were included. Fifteen studies on a total of 201 teeth investigated the structural properties, including ten (141 teeth) on microstructure and seven (60 teeth) on mineral density; six (29 teeth) investigated the mechanical properties and eleven (87 teeth) investigated the chemical properties of MIH-affected enamel and compared them to unaffected enamel. Studies unambiguously found a reduction in mineral quantity and quality (reduced Ca and P content), reduction of hardness and modulus of elasticity (also in the clinically sound-appearing enamel bordering the MIH-lesion), an increase in porosity, carbon/carbonate concentrations and protein content compared to unaffected enamel. were ambiguous with regard to the extent of the lesion through the enamel to the enamel-dentin junction, the Ca/P ratio and the association between clinical appearance and defect severity. There is an understanding of the changes related to MIH-affected enamel. The association of these changes with the clinical appearance and resulting implications for clinical management are unclear. MIH-affected enamel is greatly different from unaffected enamel. This has implications for management strategies. The possibility of correlating the clinical appearance of MIH-affected enamel with the severity of enamel changes and deducing clinical concepts (risk stratification etc.) is limited.